The business of sport - Shropshire, Kenneth L.; Rosner, Scott R. (Jones & Batlett, 2011)
The Business of Sports, Second Edition is a comprehensive collection of readings that focus on the multibillion-dollar sports industry and the dilemmas faced by today s sports business leaders. It contains a dynamic set of readings to provide a complete overview of major sports business issues. The Second Edition covers professional, Olympic, and collegiate sports, and highlights the major issues that impact each of these broad categories. The Second Edition continue to provide insight from a variety of stakeholders in the industry and cover the major business disciplines of management, marketing, finance, information technology, accounting, ethics and law. In addition, it features concise introductions, targeted discussion questions, and graphs and tables to convey relevant financial data and other statistics discussed. This book is designed for current and future sports business leaders as well as those interested in the inner-workings of the industry.